Characterizing the phenotypic effect of Xq28 duplication size in MECP2 duplication syndrome. Issue 5 (15th March 2019) - Peters, Sarika U.; Fu, Cary; Suter, Bernhard; Marsh, Eric; Benke, Timothy A.; Skinner, Steve A.; Lieberman, David N.; Standridge, Shannon; Jones, Mary; Beisang, Arthur; Feyma, Timothy; Heydeman, Peter; et al.
Abstract : Individuals with methyl CpG binding protein 2 (MECP2) duplication syndrome (MDS) have varying degrees of severity in their mobility, hand use, developmental skills, and susceptibility to infections. In the present study, we examine the relationship between duplication size, gene content, and overall phenotype in MDS using a clinical severity scale. Other genes typically duplicated within Xq28 (eg, GDI1, RAB39B, FLNA) are associated with distinct clinical features independent of MECP2. We additionally compare the phenotype of this cohort (n = 48) to other reported cohorts with MDS. Utilizing existing indices of clinical severity in Rett syndrome, we found that larger duplication size correlates with higher severity in total clinical severity scores ( r = 0.36; P = 0.02), and in total motor behavioral assessment inventory scores ( r = 0.31; P = 0.05). Greater severity was associated with having the RAB39B gene duplicated, although most of these participants also had large duplications. Results suggest that developmental delays in the first 6 months of life, hypotonia, vasomotor disturbances, constipation, drooling, and bruxism are common in MDS. This is the first study to show that duplication size is related to clinical severity. Future studies should examine whether large duplications which do not encompass RAB39B also contribute to clinical severity. Results also suggest the need for creating an MDS specific severity scale. Abstract :